2016
DOI: 10.1371/journal.pone.0156086
|View full text |Cite
|
Sign up to set email alerts
|

On the Accuracy of Genomic Selection

Abstract: Genomic selection is focused on prediction of breeding values of selection candidates by means of high density of markers. It relies on the assumption that all quantitative trait loci (QTLs) tend to be in strong linkage disequilibrium (LD) with at least one marker. In this context, we present theoretical results regarding the accuracy of genomic selection, i.e., the correlation between predicted and true breeding values. Typically, for individuals (so-called test individuals), breeding values are predicted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 69 publications
(111 reference statements)
5
75
1
2
Order By: Relevance
“…4, the observed accuracies were lower than the expected accuracies according to the formula derived by Daetwyler et al [32] when the approximation for (i.e. number of independent chromosome segments) was [48] but greater than the expected accuracy when was [49]. Our results agree with those of Neves et al [77] who reported that expected accuracies based on were higher than realized accuracies across traits; however, expected accuracies using were lower than realized accuracies in the case of within-family predictions.
Fig.
…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…4, the observed accuracies were lower than the expected accuracies according to the formula derived by Daetwyler et al [32] when the approximation for (i.e. number of independent chromosome segments) was [48] but greater than the expected accuracy when was [49]. Our results agree with those of Neves et al [77] who reported that expected accuracies based on were higher than realized accuracies across traits; however, expected accuracies using were lower than realized accuracies in the case of within-family predictions.
Fig.
…”
Section: Resultsmentioning
confidence: 75%
“…This formula depends on (heritability of the trait), (number of animals in the training population) and (the number of independent chromosome segments). was calculated by using two different approximations: (1) [48] and (2) [49], where is the effective population size, is the genome length and is the average chromosome length. Therefore, these two approximations of lead to two different estimates of .…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, Covfalse(trueY˜new,trueYnewfalse)=Op. We deduce that the variance of Ŷnew can be decomposed in the following way: VarŶnew=VarY˜new+VarYnew. By definition, according to Rabier et al (), we have A1=CovY^new,Ynew,A2+A3=VarY^new. As a consequence, we can obtain the following estimations: Cov^Ŷnew,Ynew=A^1,Var^Y^new=A^2+A^3. We have analogue estimates for trueY˜new and trueYnew.…”
Section: How To Improve the Quality Of The Predictionmentioning
confidence: 77%
“…According to formula (5) of Rabier, Barre, Asp, Charmet, and Mangin (), assuming that x 1 , …, x n are known and that ε , x new , and ε new are random, the genotypic accuracy has the following expression: ρg=βVar()xnewXV1Xβ()σe2double-struckE()‖‖xnewXV12+βXV1XVar()xnewXV1Xβ1false/2σG, where ‖‖. is the L 2 ‐norm and Var()xnew is the covariance matrix of size p × p . Note that this accuracy can be viewed as a conditional accuracy, since this expression was obtained conditionally on the TRN design matrix X .…”
Section: General Expression For the Accuracymentioning
confidence: 99%
“…The identified QTL for economically useful traits in aquaculture have been summarized recently (Abdelrahman et al, 2017). Linkage analysis to detect QTL includes family and progeny data (Rabier et al, 2016). Segregation of QTL has been studied within family.…”
Section: Introductionmentioning
confidence: 99%